2018
DOI: 10.1007/s11255-018-1880-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of kidney damage among Chinese adults with simple renal cyst

Abstract: The study revealed that SRC significantly correlated with kidney damage and special attention should be paid among Chinese adults with SRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 32 publications
1
24
1
Order By: Relevance
“…Furthermore, SRC was correlated with proteinuria (OR 1.59; 95% CI 1.30–1.95) and DeGFR (OR 1.97; 95% CI 1.56–2.47) after adjusted for potential confounders. Our results also demonstrated that maximum diameter (per 1 cm increase), bilateral location, and multiple cysts significantly correlated with DeGFR [18]. However, cross-sectional study cannot explore the causal relationship or provide an insight into the mechanisms responsible for the observed associations.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Furthermore, SRC was correlated with proteinuria (OR 1.59; 95% CI 1.30–1.95) and DeGFR (OR 1.97; 95% CI 1.56–2.47) after adjusted for potential confounders. Our results also demonstrated that maximum diameter (per 1 cm increase), bilateral location, and multiple cysts significantly correlated with DeGFR [18]. However, cross-sectional study cannot explore the causal relationship or provide an insight into the mechanisms responsible for the observed associations.…”
Section: Discussionmentioning
confidence: 75%
“…Rapid GFR decline has also been shown to be associated with CVD and all-cause mortality [17]. Previous cross-sectional observational studies demonstrated a correlation between SRC and renal injury (proteinuria or renal insufficiency) [7,18]. However, controversy remains regarding the role and possible mechanisms relating these factors to the development of renal cysts [9].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Kong et al [3] managed a large sample crosssectional study about renal cysts, whose results showed the prevalence of it among Chinese adults was 10.5% and renal cysts were significantly correlated with renal damage: the estimated glomerular filtration rate (eGFR) of 5.7% patients who with more than one renal cyst was decreased under 60 ml/min/1.73m 2 . Nowadays, according to the morphological description of renal cysts, cysts of Bosniak III, IV are symptomatic and even malignant to some extent [4].…”
Section: Introductionmentioning
confidence: 99%
“…There is a paucity of evidence about how cysts impact renal function over time, and this is likely to persist due to ethical, practical, and cost challenges associated with screening healthy or low‐risk individuals for asymptomatic renal cysts in routine practice 21 . In the general population, some cross‐sectional studies have reported inferior kidney function in individuals with renal cysts compared to those without cysts, 22‐26 while others have reported no association between cysts and renal function 27‐29 . Evidence regarding postdonation renal function among donors with cysts is limited to a single German study, which found no difference in serum creatinine among 25 donors with renal cysts compared to those without cysts (N = 243) after a mean follow‐up time of 2.8 years (1.37 vs 1.33 mg/dL in donors with and without cysts, respectively) 30 .…”
Section: Introductionmentioning
confidence: 99%